Coding of electric pulse trains presented through cochlear implants in the auditory midbrain of awake rabbit: comparison with anesthetized preparations - Chung, Yoojin; Hancock, Kenneth E; Nam, Sung-Il; Delgutte, Bertrand (The Journal of neuroscience, 2014)
Cochlear implant (CI) listeners show limits at high frequencies in tasks involving temporal processing such as rate pitch and interaural time difference discrimination. Similar limits have been observed in neural responses to electric stimulation in animals with CI; however, the upper limit of temporal coding of electric pulse train stimuli in the inferior colliculus (IC) of anesthetized animals is lower than the perceptual limit. We hypothesize that the upper limit of temporal neural coding has been underestimated in previous studies due to the confound of anesthesia. To test this hypothesis, we developed a chronic, awake rabbit preparation for single-unit studies of IC neurons with electric stimulation through CI. Stimuli were periodic trains of biphasic pulses with rates varying from 20 to 1280 pulses per second. We found that IC neurons in awake rabbits showed higher spontaneous activity and greater sustained responses, both excitatory and suppressive, at high pulse rates. Maximum pulse rates that elicited synchronized responses were approximately two times higher in awake rabbits than in earlier studies with anesthetized animals. Here, we demonstrate directly that anesthesia is a major factor underlying these differences by monitoring the responses of single units in one rabbit before and after injection of an ultra-short-acting barbiturate. In general, the physiological rate limits of IC neurons in the awake rabbit are more consistent with the psychophysical limits in human CI subjects compared with limits from anesthetized animals.